Corporeidade e a melodia da experiência estética na formação humanescente de cantores-educadores - Santos, Artemisia de Andrade e (2010)
In order for this study to be developed, the central goal on our investigation was defined as analyzing and interpreting the aesthetical experiences meanings lived by singers-educators in the human formation. The interest for the aesthetical experience theme was built from my own experience for the last twelve years as a member of the School of Music Madrigal, the oldest group in the State Federal University, created for research and cultural extension with structural perspective which brings closer teachers, students and the outer community that comes from different social realities to face the challenge of combining the ability of singing, the corporeity involvement and the aesthetical experiences meanings. This paper points out the understanding of art as perceptive expression of human emotions, such as the creation of existential demand, the restructuring of oneself and the constructions which shape beauty. We seek a dense contribution of new challenges to the peculiar demand of human potential in terms of sensibility repertoire, of involvement, of expectation in magnifying the possibilities and the human and social competences. In the formation human process, we find a living field blooming with natural artistical possibilities, experimenting emotions and feelings shared in collective life, and bringing out impulses to unexpected ludic creation, establishing a powerful aesthetical ambience which highlights the symbolic and imaginary with the deepening of rich ludopoiese properties in several meanings. From the guiding principles of etnophenomenology we find structural and indispensable perspectives which contemplate values, desires, archtype images and ideas that impress originality and fertility to the study. On this path we understand the abundance of living moments of intense commitment, acquaintance, challenges, reunions and connections that stand out from fundamental aspects to freedom, autonomy, creativity and new discontinuities. This acknowledgement brings us closer to the enlighted fullness which makes us humans